Gestational diabetes mellitus and obstetric outcomes in a Ghanaian community - Bawah, Ahmed Tijani; Ngala, Robert Amadu; Seini, Mohammed Mustapha; Ussher, Francis Abeku; Alidu, Huseini; Kwame Wumbee, Joshua Dokurugu; Yeboah, Francis Agyeman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study was aimed at evaluating effect of Gestational diabetes mellitus (GDM) and maternal characteristics on pregnancy outcomes. GDM has several risk factors including; advanced maternal age, ethnic background, obesity and family history of diabetes mellitus. These pregnancy complications are associated with fetal morbidity and mortality and may lead to macrosomia and shoulder dystocia. Others are stillbirth, miscarriages, preterm and small for gestational age babies. Methods: This was a retrospective case-control study which compared maternal characteristics and pregnancy outcome among pregnant women with and without GDM. Diagnosis of GDM was done in accordance with the American Diabetes Association (ADA) criteria. Weight and height were determined and Body mass index (BMI) calculated. Pregnancy outcome was determined at the end of pregnancy and information on maternal characteristics obtained using questionnaire and patient folders. Results: Those who developed GDM were significantly older (OR=1.772; 95% CI=1.432-2.192; P<0.0001) and had higher BMI (OR=1.637; 95% CI=1.004-1.289; P=0.044) than those who did not. A significant number of those who developed GDM also had stillbirths (OR= 5.188; 95% CI=1.093-24.613; p=0.038) and cesarean deliveries (OR=14.362; 95% CI=3.661-56.335; p= 0.001). Conclusions: Women who develop GDM are more likely to deliver stillborn or macrosmic babies and may require surgical intervention in order to have normal deliveries.